Development of Authentic Assessment Instrument For Performance in Learning Mathematics in Linear Program - Arifin, Zainul; Kartono, Kartono; Supriyadi, Supriyadi (Journal of Research and Educational Research Evaluation, 2018)
Problems often faced by teachers of mathematics, namely the validity and reliability of measuring instruments assessment of performance, preparation of test performance is still very limited knowledge and understanding of teachers, the assessment results are often influenced by the objectivity of the teacher as a rater because in doing the assessment is done without the involvement of other teachers as collaborator. This study aims to examine the level of validity, reliability, and the practicality of authentic assessment instruments for performance in linear mathematics learning programs. The instrument is useful for teachers to innovate in the world of education and for students as study material to determine the level of understanding of students' abilities. This research method uses research and development techniques. The sample was used for a study of 34 students for small-scale tests and 44 students for large-scale tests. The results showed that the instrument was declared to be valid in the contents of 0.83. ICC reliability estimation between assessors 0.730. The scale test shows the value of KMO 0.548 and Barteletts sig test. 0,000. But there is one item that has an MSA value <0.5. Large scale test shows the value of KMO 0,532 and Bartlett's Test sig. 0,000. All items obtained MSA value> 0.5. The instrument forms 2 components. The value of Eigenvalues ​​component 1 is 2, 007 and component 2 is 1.183. The estimated reliability of the instrument on a small scale test was 0.674 and a large scale of 0.661. Practical test gets a score of 155. The conclusion of this study is that the instrument developed has proven to be valid, reliable and practical. Very practical proven instruments based on teacher ratings. The suggestion of this research is for teachers to use this instrument in learning linear mathematics programs to produce easy and precise measurements.